Da relevância das soluções adequadas para os conflitos fundiários urbano - Araújo, João Priolli de (2024)
This dissertation seeks a doctrinal conceptualization that allows a more strategic and holistic view of urban land conflicts (understood here in a broad and narrow perspective), our object of study, in order to include the largest number of actors involved in tackling what is, and always has been, one of Brazil's most serious problems. The aim is to seek, within the influences of (neo)constitutionalist theory and post-positivist philosophy, how “appropriate solutions” can be constructed for urban conflicts and, not least, to allocate them within the legal system that we understand to be most pertinent to their treatment by the Judiciary, Legislative and Executive branches: Constitutional Urban Law. The hermeneutic horizons for “adequate solutions” to urban land conflicts can be found through the exercise of concrete weighing and balancing and by respecting the multiple possibilities of combining the spheres of protection of five principle-norms: the right to cities, the right to adequate housing (and protection against evictions and forced removals), the social function of cities, the social function of urban property and, finally, the democratic management of cities and urban spaces